The Performance and Kinetic Study of Membrane Anaerobic System (MAS) in Treating Pome - Lai, Long Seng (1999)
Anaerobic digestion has been proven to be the most efficient process for primary treatment of POME. However a major problem in the anaerobic wastewater treatment process is to maintain the sufficient quantity of active biomass in the reactor. In this study membrane separation technology has been applied after anaerobic digestion to increase solids retention time and improve treatment efficiency. The objectives of the study are to evaluate the overall membrane anaerobic system (MAS) treatment efficiency and the applicability of three known kinetic models on the system and determination of kinetic coefficients. The MAS consists of a cross-flow ultrafiltration membrane (PCI Micro 240) for solid-liquid separation. Six steady states were ottained over a range of mixed liquor suspended solids of 12,681 - 30,460 mgtl. The study showed a good fitting of the Monod Model (91.1%), Contois Model (98.5%) and Chen and Hashimoto Model (95%) for the MAS treating raw POME at organic loadings between 1.5 kgCOD/m3/d to 6.5 kgCOD/m3/d. The growth yield coefficient Y, was found to be 0.604 kg VSSlkgCOD while the specific microorganism decay rate was 0.099 day-to The k values were in the range of 0.242 to 0.425 mg COD/mg VSS.d and the Pm values were between 0.145 to 0.257dail. The Monod Model and Chen and Hashimoto Model are better than the Contois Model for solids retention time (SRT), effluent substrate concentration (S) and substrate utilisation rate (E) estimation. Both models are able to produce a good predicted S and E if the SRT >= 50 days. Throughout the study, the removal efficiency of COD was 83.2 to 97.97 %. The methane production rate was between 0.262 to 0.473 1/g-COD utilised/d The MAS treatment efficiency was greatly affected by SRT and OLRs. In this study, membrane fouling and polarization at the membrane surface played a significant role in the formation of a strongly attached cake layer limiting membrane permeability.